ACETYLSALICYLIC ACID: CONTROVERSIAL AND OUTSTANDING ISSUES - E. N. Dankovtseva (Столичная издательская компания, 2015)
Review of current ideas about the role of acetylsalicylic acid (ASA) in the primary prevention of cardiovascular disease is presented. Data on reduction in malignant neoplasms incidence rate in long-term use of the drug, as well as prospects for further study of ASA in the primary prevention are considered.